Rain drop pigmentation in chronic arsenic poisoning - Anupam Das; Anand Toshniwal; Kunal Majumdar (Wolters Kluwer Medknow Publications, 2020)
Contamination of ground water with arsenic is a problem being faced by over 30 countries in the world, since a few decades. Arsenicosis is a multisystem disorder characterised by cutaneous, gastrointestinal, urological and hematological manifestations. The WHO defines arsenicosis as a chronic health condition arising from prolonged ingestion (not less than 6 months) of arsenic above a safe dose, usually manifested by characteristic skin lesions, with or without involvement of internal organs. The WHO guideline for arsenic in drinking water is 0.01mg/ml. Cutaneous lesions are the earliest manifestations characterised by mottled pigmentation of covered areas of body called as rain drop pigmentation, blotchy mucosal pigmentation, depigmentation, palmoplantar pitting and keratosis.[1] Cutaneous malignancies which can be caused by arsenicosis include bowens disease, squamous cell carcinoma, basal cell carcinoma and melanoma.[2] It can also cause ischemic heart disease, hepatosplenomegaly, black foot disease and internal malignancies. [3]